Omicron Subvariants: Clinical, Laboratory, and Cell Culture Characterization. (11th November 2022) - Morris, C Paul; Eldesouki, Raghda E; Sachithanandham, Jaiprasath; Fall, Amary; Norton, Julie M; Abdullah, Omar; Gallagher, Nicholas; Li, Maggie; Pekosz, Andrew; Klein, Eili Y; Mostafa, Heba H
Abstract: Background: The variant of concern Omicron has become the sole circulating severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variant for the past several months. Omicron subvariants BA.1, BA.2, BA.3, BA.4, and BA.5 evolved over the time, with BA.1 causing the largest wave of infections globally in December 2021–January 2022. This study compared the clinical outcomes in patients infected with different Omicron subvariants and the relative viral loads and recovery of infectious virus from upper respiratory specimens. Methods: SARS-CoV-2–positive remnant clinical specimens, diagnosed at the Johns Hopkins Microbiology Laboratory between December 2021 and July 2022, were used for whole-genome sequencing. The clinical outcomes of infections with Omicron subvariants were compared with infections with BA.1. Cycle threshold (Ct) values and the recovery of infectious virus on the VeroTMPRSS2 cell line from clinical specimens were compared. Results: BA.1 was associated with the largest increase in SARS-CoV-2 positivity rate and coronavirus disease 2019 (COVID-19)–related hospitalizations at the Johns Hopkins system. After a peak in January, cases decreased in the spring, but the emergence of BA.2.12.1 followed by BA.5 in May 2022 led to an increase in case positivity and admissions. BA.1 infections had a lower mean Ct value when compared with other Omicron subvariants. BA.5 samples had a greater likelihood of having infectious virus at Ct values <20. Conclusions: Omicron subvariants continue to be associated with a relatively high rate of polymerase chain reaction (PCR) positivity and hospital admissions. The BA.5 infections are more while BA.2 infections are less likely to have infectious virus, suggesting potential differences in infectibility during the Omicron waves. Abstract : The BA.1 subvariant was associated with the largest increase in case numbers and admissions (January 2022), followed by a smaller but steady increase in May–July 2022 that was associated with the subvariants BA.2.12.1 and BA.5.